Effects of COVID-19 on society and sport a national response - Begovic, M. (Managing Sport and Leisure, 2020)
This paper represents a continuation of the Parnell et al. (2020) commentary on the outbreak of COVID-19. In times of crisis, a country`s resilience, its institutional response, economy, and socio-political dynamics are put to the test. Montenegro, like many other countries, is ill-prepared for tackling the unprecedented health challenge that COVID-19 represents as well as the compounding broader economic and socio-political implications. The government of Montenegro established the National Coordination Body for Communicable Diseases (NKT). Even though the NKT is set as a multisectoral and multidisciplinary body to coordinate the implementation of the broader health and socio-economic measures, no representative from the Montenegro`s sport system has taken part in decision-making processes. Although economic dimension has been highlighted, the social and health values of sport and physical activity have been neglected largely undermining their crucial potential for addressing maintaining activities while respecting physical distancing policies, in the context of restricted movement.